Hubungan antara Jumlah Dana yang Dihimpun, Kredit yang Diberikan dan Fee Based Income dengan Tingkat Pengembalian Aset pada Perbankan Go Public, Periode 2003 Hingga 2007 - Pariang Siagian (The Winners, 2010)
To evaluate the financial performance that has been achieving, it is not just doing by physical performance and interesting promotion, but could be examined by scientific methods and principles, such as financial statements analysis, which Central Bank has been done. Because, to know the reality of successful company includes banking, it could be done by measuring those financing performance. For instance, by doing the financial ratios analysis with comparing and interpreting an account to another or others accounts from financial statements that has assumed being necessary and can  be give much benefits.